WinChannel's digital gambit to revitalize rural China. Issue 1 (7th February 2019) - Moran, Peter; Chng, Daniel Han Ming; Zhao, Liman
Abstract : Learning outcomes: Following are the learning outcomes: to understand how the tools and frameworks of strategic analysis can be applied to understand the evolution of value creation and capture in the FMCG industry; to analyze the core competencies of a company and understand their relevance in this fast-changing industry; to understand how to evaluate the pros and cons of a certain strategy and business model; and to develop strategic recommendations. Case overview/synopsis: The case series traces the developments in China's FMCG industry from the early 2010s to 2017, in general, and the efforts of Beijing WinChannel Software Technology Co., Ltd. (WinChannel) and its affiliated company, Huixiadan, in their attempt to apply new digital technologies to transform the traditional trade channel, in particular. The decision point of Case A, in early 2015, is how WinChannel can help improve the reach and efficiency of the traditional trade channel and wonders if the emerging online/mobile B2B FMCG platforms are the right solution for the increasingly digitized FMCG retail industry in China. The decision point of Case B, at the end of 2017, is how could Huixiadan's business model be sustainable and what it should do to withstand the competitive threats even as it tries to exploit opportunities in the traditional FMCG industry in China. Complexity academic level: It can be used with MBAs, EMBAs and senior executives. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS: 11: Strategy.